Exploring the Challenges of the Non-Directive Attitude in Person-Centred Counselling in Indonesian Culture - Sutanti , Natri (KnE Social Sciences, 2019)
Indonesian culture has inﬂuenced the way people perceive counselling, which shows the tendency towards avoidance attitudes. The situation presents a challenge towards the feasibility of person-centred counselling to be applied in Indonesia, as the counselling approach tends to come across with Indonesian culture. This paper aims to critically discuss the potential challenges of working with the Indonesian client from a cultural point of view and the readiness of a counsellor in terms of knowledge about non-directive counselling by reviewing some literature in depth. The exploration of the challenges shows that the biggest obstacle to applying the non-directive attitude in Indonesia is the factor of the difﬁculty to obtain a comprehensive understanding of the non-directive concept rather than the factor of cultural difference. However, this challenge can be handled by understanding the concept of principled and instrumental non-directiveness which gives a view of ﬂexibility and the broaden meaning of the non-directive attitude. Conclusively, there are no exclusions, limitations or boundaries from the person-centred approach that can convince the impossibility of becoming a non-directive counsellor in the Indonesian culture. The presence of inevitable challenges arising from the culture of Indonesia will not signiﬁcantly affect the counsellor, if the non-directive attitudes have become part of the counsellor’s self-concept. Keywords: challenges; non-directive; person-centred counselling; Indonesian culture